Influence of Low Molecular Weight Heparin on the Hemostatic System After Abdominal Surgery - Schmitz-Huebner, U; Rüschemeyer, C; Schulte, H; Loo, J van de (Thrombosis and Haemostasis, 1985)
The hemostatic effect of two low molecular weight heparin fractions and of one unfractionated heparin preparation administered subcutaneously b. i. d. was examined in 6 healthy subjects and in 53 patients after major abdominal surgery. Among other tests platelet count, prothrombin time, fibrinogen, β-thrombo- globulin, antithrombin, antiplasmin, FPA and F-CB 3 related antigen, as well as various heparin activities, were repeatedly determined pre- and postoperatively. Under all tested conditions the low molecular weight fractions induced higher heparin levels, both in terms of anti-Xa and of anti-thrombin activity. No further significant differences of the laboratory results between the treatment groups were documented. Total blood loss measured at the first postoperative day was higher in patients with malignancy and negatively correlated with antithrombin and antiplasmin levels, while no relation was observed with the heparin activities and the other tested parameters. Whereas evidence for a hemorrhagic property of the tested low molecular weight heparin fractions was found, a particular mechanism underlying this effect could not be identified.
Keywords: Thrombosis prophylaxis; Low molecular weight heparin; Postoperative hemostasis; Bleeding complications